Poor diet quality among Brazilian adolescents with HIV/AIDS - Luana Fiengo Tanaka; Maria do Rosário Dias de Oliveira Latorre; Aline Medeiros da Silva; Thais Claudia Roma de Oliveira Konstantyner; Elissa Caroline Mendes; Heloísa Helena Sousa Marques (Elsevier, 2015)
OBJECTIVE: This study aimed to assess diet quality among adolescents with HIV/AIDS. METHOD: A cross-sectional study was conducted involving patients with HIV/AIDS treated in a referral hospital in Sao Paulo, Brazil. Eighty-eight adolescents (10-19 years of age) participated in the study. Information on disease history and use of medication were obtained from medical records. The participants responded to two 24-hour diet recalls. Diet quality was assessed by means of the Healthy Eating Index-2005 (HEI-2005) adapted to the Brazilian population. Pearson's correlation coefficients were calculated. Mean HEI-2005 scores were compared according to the independent variables using either the Student's t-test or the Mann-Whitney test. RESULTS: The mean HEI-2005 score was 51.90 (SE = 0.90). The components with the lowest means were whole grains and sodium. Components with highest means were total grains and oils. No correlations were found between the independent variables and HEI score. Adolescents living in foster homes had higher means for total fruit and lower means for meat and beans in comparison to adolescents living with their families. Girls had higher means for milk and lower means for calories from solid fats, alcoholic beverages, and added sugars in comparison to boys. CONCLUSIONS: Adolescents with HIV/AIDS exhibited a similar eating pattern to that of adolescents in the general population: high consumption of added sugar, saturated fat, and sodium, and insufficient ingestion of whole grains and fruits. Special attention should be paid to the diet of adolescents with HIV/AIDS, who are at greater risk of developing cardiovascular and other chronic diseases.